Catalytically active and chemically inert CdIn2S4 coating on a CdS photoanode for efficient and stable water splitting. Issue 19 (9th May 2017) - Song, Ji-Peng; Yin, Peng-Fei; Mao, Jing; Qiao, Shi-Zhang; Du, Xi-Wen
Abstract : A catalytically active and chemically CdIn2 S4 layer was coated on CdS nanoflakes to improve the stability and even photocurrent of photoelectrochemical (PEC) water splitting. Abstract : Cadmium sulfide was popularly utilized as a light harvesting material for photoelectrochemical (PEC) water splitting, however, the drawback of poor durability limits its practical application. Herein, we show that a catalytically active and chemically inert cadmium indium sulfide (CdIn2 S4 ) can improve the stability and even photocurrent of a CdS photoelectrode.